Milestones and Turning Points in Development Thinking
XVII, 319 p.
Keywords: The first volume of IDS Companions to Development Studies focuses on pivotal writing emerging from the IDS fellowship during the last 50 years. It includes five topics: perspectives and paradigms, debunking myths, development policy, gender and international perspectives, and policy, as well as names like Seers, Singer, Lipton, Reg Green.